2022
DOI: 10.3390/ijerph19073809
|View full text |Cite
|
Sign up to set email alerts
|

Do Autistic Traits Correlate with Post-Traumatic Stress and Mood Spectrum Symptoms among Workers Complaining of Occupational Stress?

Abstract: The adult autism subthreshold spectrum model appears to be a useful tool for detecting possible vulnerability factors in order to develop mental disorders in the contest of work-related stress. The aim of the present study is to analyze the relationship between autism, mood, and post-traumatic spectrum in a cohort of subjects complaining of work-related stress before the COVID-19 pandemic. The authors carried out a retrospective investigation of both medical records and self-assessment tools of a sample of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These results align with McConachie et al's [43] findings that autistic people indicated being positive about their autistic identity as a central aspect particularly relevant to their quality of life. Furthermore, considering the diversity of the ASD diagnosis and the increasing attention in the literature on subthreshold forms of autism [44], assessing the personal aspects, such as illness identity, may be beneficial to understand abilities, feelings, and challenges.…”
Section: Discussionmentioning
confidence: 99%
“…These results align with McConachie et al's [43] findings that autistic people indicated being positive about their autistic identity as a central aspect particularly relevant to their quality of life. Furthermore, considering the diversity of the ASD diagnosis and the increasing attention in the literature on subthreshold forms of autism [44], assessing the personal aspects, such as illness identity, may be beneficial to understand abilities, feelings, and challenges.…”
Section: Discussionmentioning
confidence: 99%
“…In this framework, it is interesting to acknowledge that catatonic symptoms and autistic traits have been found to be particularly prevalent on the BPD population ( 19 , 49 , 50 ). Moreover, previous studies already reported how in both BPD and catatonia a higher prevalence of autistic traits would be associated with a greater severity of the manifestations and an increased suicidal risk ( 51 53 ).…”
Section: Introductionmentioning
confidence: 96%
“…For example, Davis et al [ 24 ] reported that the social and non-social facets of autistic traits differentially predicted social cognitive processes in a sample of college students. Additionally, the various facets of autism traits appear to be connected with sensory processing in adults with typical development in diverse ways [ 25 , 26 ]. The interest in focusing on subthreshold autistic traits lies in the fact that they seem to exert a detrimental effect on quality of life, being also a significant vulnerability factor for the development of other psychiatric disorders, as well as suicidal thoughts and behaviors [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the various facets of autism traits appear to be connected with sensory processing in adults with typical development in diverse ways [ 25 , 26 ]. The interest in focusing on subthreshold autistic traits lies in the fact that they seem to exert a detrimental effect on quality of life, being also a significant vulnerability factor for the development of other psychiatric disorders, as well as suicidal thoughts and behaviors [ 26 , 27 , 28 ]. As the autism spectrum is frequently closely associated with other features beyond its core characteristics, two of which are alexithymia [ 29 , 30 ] and anxiety [ 31 , 32 ], understanding the structure of autism traits and supporting their adequate measurement allows for the further assessment of the relationship between these traits and other variables of interest in the spectrum.…”
Section: Introductionmentioning
confidence: 99%